Розповсюдження Iva xanthifolia (Nutt) Fresen на південному сході України - Прохорова, С.І. (Промышленная ботаника, 2004)
The distribution of Iva xanthiifolia (Nutt.) Fresen. in the south-east of Ukraine has been studied according to the data of DNZ, KW herbaria and expeditional investigations. The species has been fixed in the territories of plants, on mine waste dumps, cultivated lands, in settlement areas, especially in ruderal growth sites and in vacant lots, along railways and motor roads. Lately, Iva xanthiifolia has been intruding into local phytocenoses, therefore it is possible to assert that this species has become an agraphyte in the south-east of Ukraine.